2020
DOI: 10.2298/jsc200425050d
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical properties of the deep eutectic solvents with triethanolamine as a major component

Abstract: Different deep eutectic solvents (DESs) of triethanolamine (TEOA) and oxalic acid (OA), glacial acetic acid (AA), L-(+)-lactic acid (LA), oleic acid (OLA), glycerol (G), ethylene glycol (EG), propylene glycol (PEG), choline chloride (ChCl) or 1,3-dimethylurea (DMU) were prepared and characterized re-garding their physicochemical (density, viscosity, electrical conductivity, refract-tive index, coefficient of volume expansion, molecular volume, lattice energy, and heat capacity) properties ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Different component ratios (i.e., 1:2, 1:5, 1:10, and 1:20, denoted as ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 , respectively) of solid ChCl and TEOA were mixed by stirring and heating to form a homogeneous colorless liquid (Figure a). Raman spectra revealed that the components’ characteristic peaks of C–N (at ∼724 cm –1 ) and C–H (at 2800–3100 cm –1 ) in ChCl and C–O (at 800–960 cm –1 and ∼1050 cm –1 ) and O–H (at 3100–3600 cm –1 ) in TEOA coexist in ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 (Figure b), demonstrating the formation of ILAs due to the weak interactions between H-bond donors and H-bond acceptors, such as O–H···O, O–H···Cl, and O–H···N, as well as the additional Coulombic action between ions . The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm –1 ), weak (at ∼3382 cm –1 ), and non-H-bonds (at ∼3478 cm –1 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different component ratios (i.e., 1:2, 1:5, 1:10, and 1:20, denoted as ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 , respectively) of solid ChCl and TEOA were mixed by stirring and heating to form a homogeneous colorless liquid (Figure a). Raman spectra revealed that the components’ characteristic peaks of C–N (at ∼724 cm –1 ) and C–H (at 2800–3100 cm –1 ) in ChCl and C–O (at 800–960 cm –1 and ∼1050 cm –1 ) and O–H (at 3100–3600 cm –1 ) in TEOA coexist in ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 (Figure b), demonstrating the formation of ILAs due to the weak interactions between H-bond donors and H-bond acceptors, such as O–H···O, O–H···Cl, and O–H···N, as well as the additional Coulombic action between ions . The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm –1 ), weak (at ∼3382 cm –1 ), and non-H-bonds (at ∼3478 cm –1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity of ILAs was measured with a rheometer (DHR-1, TA). Their morphologies and element contents were analyzed by scanning electron microscopy (SEM, FEI Scios 2 HiVac, 31 The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure 1c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm −1 ), weak (at ∼3382 cm −1 ), and non-H-bonds (at ∼3478 cm −1 ). 27 The H-bonding interactions of ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 mainly consist of strong and weak H-bond components.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This has become a topic of great interest for researchers in various fields utilizing DESs. 13,14 Previous studies on DES properties have mainly focused on the effect of temperature, 16,17 with only a few reports considering the effect of chemical structure and component proportion. [18][19][20] Several computational modeling methods have been developed in recent years for predicting the density and viscosity of DESs.…”
Section: Introductionmentioning
confidence: 99%